The effect of cinnamon on pain among teenage girls with primary dysmenorrhea in Lampung Indonesia - Yulistiana Evayanti; Sri Andayani Hidayat (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2019)
Background: Dysmenorrhea is an event that occurs during menstruation that occurs and causes teenage girls are absent from school and daily activities. Based on the results of the survey on November at Bandar Lampung high school, of the 10 teenage girls who had menstruation as many as 7 (70%) often complian of severe pain during menstruation.Purpose: Knowning the effect of cinnamon on pain among teenage girls with primary dysmenorrhea in Lampung IndonesiaMethods: The quantitative research, the design of this study is Pre-experimental with the on-group pretest-posttest approach. The population was teenage girls in grade X and XI at Bandar Lampung high school and samples were 30 teenagers. Sampling of this research was using purposive sampling technique which was carried out from April, 2019 to Juli, 2019. The analysis used univariate analysis and bivariate analysis using the T test.Results: The mean of dysmenorrhea before consumption was 6.67 and after consumption was 2.13 . The effect of cinnamon on pain among teenage girls with primary dysmenorrhea with p-value 0.00 <0.05.Conclusion: The significant effect of cinnamon on pain among teenage girls with primary dysmenorrheain at Bandar Lampung 13th high school in 2019. Finding in this study could be applied as alternative therapy for teenager and further research need more deep exlporation.